Health Education Using Booklet and Diary Media on the Self-Efficacy of Housewives with Hypertension - Rasdiyanah, Rasdiyanah; Wiarsih, Wiwin; Sukihananto, Sukihananto (Universitas Pendidikan Indonesia, 2020)
ABSTRACTHealth education is one of intervention strategies in nursing. Optimization in its implementation requires media support, health promotion media that can be used are booklet and diary. Booklet provides more information and diary records daily activities. This research aimed to identify the effect of health education using booklet and diary on the self-efficacy of housewives with hypertension in Depok. This quasi experimental research used pre-post design with control group. The sampling technique used non probability sampling with consecutive sampling method. The total of samples were 66 respondents. Data were collected using an Indonesian version of the High Blood Pressure – Self Care Profile and analyzed using descriptive statistics. The result of independent t test showed significant effect in the mean of self-efficacy value after health education using booklet and diary (p value = 0.002 0.05). In conclusion, health education using booklet and diary media could increase the self-efficacy of housewives. This health education needs to be applied to clients with hypertension to increase self-efficacy in conducting self-management. ABSTRAKPendidikan kesehatan merupakan salah satu strategi intervensi dalam keperawatan. Optimalisasi dalam pelaksanaannya memerlukan dukungan media, media promosi kesehatan yang dapat digunakan diantaranya adalah booklet dan diary. Booklet memuat lebih banyak informasi dan diary mencatat aktivitas sehari-hari. Tujuan penelitian ini adalah untuk mengidentifikasi pengaruh pendidikan kesehatan menggunakan booklet dan diary terhadap efikasi diri ibu rumah tangga dengan hipertensi di Kota Depok. Penelitian quasi eksperiment ini menggunakan pre-post design with control group. Teknik sampling menggunakan non probability sampling dengan metode consecutive sampling. Total sampel sebanyak 66 responden. Data dikumpulkan menggunakan versi Indonesia High Blood Pressure – Self Care Profile dan dianalisis menggunakan statistik deskriptif. Hasil Independent t test menunjukkan pengaruh signifikan pada rata-rata nilai efikasi diri setelah pendidikan kesehatan menggunakan booklet dan diary (p value= 0,002 0,05). Sebagai kesimpulan bahwa pendidikan kesehatan menggunakan booklet dan diary dapat meningkatkan efikasi diri ibu rumah tangga. Pendidikan kesehatan ini perlu diterapkan pada klien dengan hipertensi untuk meningkatkan keyakinan diri dalam melakukan manajemen diri.